The role of conductive nanoparticles in anaerobic digestion: Mechanism, current status and future perspectives - Kumar, Smita S.; Ghosh, Pooja; Kataria, Navish; Kumar, Deepak; Thakur, Sveta; Pathania, Deepak; Kumar, Vivek; Mohd, Nasrullah; Singh, Lakhveer (Elsevier, 2021)
In the current scenario, alternative energy sources are the need of the hour. Organic wastes having a larger fraction of biodegradable constituents present a sustainable bioenergy source. It has been reported that the calorific value of biogas generated by anaerobic digestion (AD) is 21e25 MJ/m3 with the treatment which makes it an excellent replacement of natural gas and fossil fuels and can reduce more than 80% greenhouse gas emission to the surroundings. However, there are some limitations associated with the AD process for instance ammonia build-up at the first stage reduces the rate of hydrolysis of biomass, whereas, in the last stage it interferes with methane formation. Owing to special physicochemical properties such as high activity, high reactive surface area, and high specificity, tailor-made conductive nanoparticles can improve the performance of the AD process. In the AD process, H2 is used as an electron carrier, referred as mediated interspecies electron transfer (MIET). Due to the diffusion limitation of these electron carriers, the MIET efficiency is relatively low that limits the methanogenesis. Direct interspecies electron transfer (DIET), which enables direct cell-to-cell electron transport between bacteria and methanogen, has been considered an alternative efficient approach to MIET that creates metabolically favorable conditions and results in faster conversion of organic acids and alcohols into methane. This paper discusses in detail the application of conductive nanoparticles to enhance the AD process efficiency. Interaction between microbes in anaerobic conditions for electron transfer with the help of CNPs is discussed. Application of a variety of conductive nanomaterials as an additive is discussed with their potential biogas production and treatment enhancement in the anaerobic digestion process.